Revision of the Afro-Madagascan genus Costularia (Schoeneae, Cyperaceae): infrageneric relationships and species delimitation - Isabel Larridon; Linah Rabarivola; Martin Xanthos; A. Muthama Muasya (PeerJ, 2019)
A recent molecular phylogenetic study revealed four distinct evolutionary lineages in the genus Costularia s.l. (Schoeneae, Cyperaceae, Poales). Two lineages are part of the Oreobolus clade of tribe Schoeneae: the first being a much-reduced genus Costularia s.s., and the second a lineage endemic to New Caledonia for which a new genus Chamaedendron was erected. The other two lineages were shown to be part of the Tricostularia clade of tribe Schoeneae. Based on morphological and molecular data, the genus Costularia is here redelimited to represent a monophyletic entity including 15 species, which is restricted in distribution to southeastern Africa (Malawi, Mozambique, South Africa, Swaziland, Zimbabwe), Madagascar, the Mascarenes (La Réunion, Mauritius), and the Seychelles (Mahé). Molecular phylogenetic data based on two nuclear markers (ETS, ITS) and a chloroplast marker (trnL-F) resolve the studied taxa as monophyletic where multiple accessions could be included (except for Costularia laxa and Costularia purpurea, which are now considered conspecific), and indicate that the genus dispersed once to Africa, twice to the Mascarenes, and once to the Seychelles. Two endemic species from Madagascar are here described and illustrated as new to science, as is one additional species endemic to La Réunion. Two taxa previously accepted as varieties of Costularia pantopoda are here recognised at species level (Costularia baronii and Costularia robusta). We provide a taxonomic revision including an identification key, species descriptions and illustrations, distribution maps and assessments of conservation status for all species.